Two Dimensional Honeycomb Materials: Random Fields, Dissipation and Fluctuations - Frederico, T.; Oliveira, O.; de Paula, W.; Hussein, M. S.; Cardoso, T. R. [UNESP] (Springer Nature, 2017)
In this paper, we propose a method to describe the many-body problem of electrons in honeycomb materials via the introduction of random fields which are coupled to the electrons and have a Gaussian distribution. From a one-body approach to the problem, after integrating exactly the contribution of the random fields, one builds a non-hermitian and dissipative effective Hamiltonian with two-body interactions. Our approach introduces besides the usual average over the electron field a second average over the random fields. The interplay of two averages enables the definition of various types of Green’s functions which allow the investigation of fluctuation-dissipation characteristics of the interactions that are a manifestation of the many-body problem. In the current work, we study only the dissipative term, through the perturbative analysis of the dynamics associated the effective Hamiltonian generated by two different kinds of couplings. For the cases analyzed, the eigenstates of the effective Hamiltonian are complex and, therefore, some of the states have a finite life time. Moreover, we also investigate, in the mean field approximation, the most general parity conserving coupling to the random fields and compute the width of charge carriers Γ as a function of the Fermi energy EF. The theoretical prediction for Γ(EF) is compared to the available experimental data for graphene. The good agreement between Γtheo and Γexp suggests that description of the many-body problem associated to the electrons in honeycomb materials can indeed be done via the introduction of random fields.
Keywords: Graphene; Many-body; Random fields